Association between geriatric nutritional risk index and overactive bladder in the elderly population: a cross-sectional study - Wei Zheng; Wei Zheng; Chuanzan Zhou; Jia Miao; Yunkai Yang; Xuanhan Hu; Heng Wang; Xinyu Zhang; Qi Zhang; Yifan Wang (Frontiers in Nutrition)
BackgroundThe prevalence of overactive bladder (OAB) is increasing in the elderly population and there is growing evidence that malnutrition affects the urinary system. Despite this, research on the relationship between nutritional factors and OAB remains limited.MethodsWe included 17,161 elderly individuals from the National Health and Nutrition Examination Survey conducted between 2005 and 2018. Overactive Bladder Symptom Scores (OABSS) were utilized to assess symptoms of OAB. A multifactorial logistic regression analysis was employed to evaluate the independent association between the Geriatric Nutritional Risk Index (GNRI) and the prevalence of OAB. Restricted cubic spline plots examined the potential non-linear relationship between GNRI and OAB. Influencing factors were assessed through subgroup analyses, while the predictive utility of GNRI was assessed with receiver operating characteristic (ROC) curves. The influence of inflammatory response and cognitive function on the interaction between GNRI and OAB was also examined by mediation analysis.ResultsGNRI in the OAB group was significantly lower than that in the non-OAB group. Multifactorial logistic regression analysis revealed that GNRI significantly predicts OAB (p < 0.05). The Restricted Cubic Spline (RCS) curve indicated a non-linear negative correlation between GNRI and the risk of OAB in the elderly (non-linear p = 0.0029). In receiver operating characteristic analysis, GNRI outperforms serum albumin or body mass index (BMI) alone in predicting OAB risk. The study revealed that inflammatory response mediates the relationship between GNRI and OAB, while cognitive function has a relatively weaker influence on the strength of the association between GNRI and OAB.ConclusionGNRI serves as a reliable predictive marker for OAB in the elderly population, demonstrating a nonlinear inverse correlation with OAB prevalence. Furthermore, this study elucidates the underlying inflammatory mechanisms that link GNRI to the development of OAB.